Penerapan Metode Weighted Aggregated Sum Product Assessment Dalam Penentuan Penerima Beasiswa Bidik Misi - Royanti Manurung; Fitriani Fitriani; Fince Tinus Waruwu; Fadlina Fadlina (STMIK Budi Darma, 2018)
The scholarship is an existing work program in every university or university. The scholarship program is held to ease the burden of students in taking the study period, especially in the matter of cost. The scholarship is given selectively in accordance with the type of scholarship holders. Lots of scholarships are offered to outstanding and underprivileged students. One of the scholarships offered is the Bidik Misi scholarship. In this study used WASPAS method so that the results obtained are expected to help the universities in managing the Bidik Misi Scholarship to decide the prospective scholarship recipients who are entitled to receive the Bidik Misi.